Optimal rationing within a heterogeneous population. (25th August 2016) - Choné, Philippe; Gauthier, Stéphane
Abstract : A government agency delegates to a provider (hospital, medical gatekeeper, school, social worker) the decision to supply a service or treatment to individual recipients. The agency does not perfectly know the distribution of individual treatment costs in the population. The single‐crossing property is not satisfied when the uncertainty pertains to the dispersion of the distribution. We find that the provision of service should be distorted upward when the first‐best efficient number of recipients is sufficiently high.